Schwannomas in the head and neck: retrospective analysis of 21 patients and review of the literature - Langner, Erwin (2007)
CONTEXT AND OBJECTIVE: Schwannomas are benign neoplasms of the peripheral nerves originating in the Schwann cells. According to their cellularity, they can be subdivided into Antoni A or Antoni B types. They are rare and usually solitary, with clearly delimited capsules. They occur in the head and neck region in only 25% of the cases, and may be associated with Von Recklinghausen’s disease. The present study retrospectively analyzed some data on this disease in the head and neck region and reviewed the literature on the subject. DESIGN AND SETTING: Retrospective study at Head and Neck Service, Universidade Estadual de Campinas. METHODS: Data on 21 patients between 1980 and 2003 were reviewed. The sites of cervical schwannomas and the intraoperative, histopathological and postoperative clinical status of these cases were studied. Diagnostic methods, type of surgery and association with neurofi bromatosis were evaluated. RESULTS: The patients’ ages ranged from 16 to 72 years. Four patients had a positive past history of type I neurofi bromatosis or Von Recklinghausen’s disease. The nerves affected included the brachial and cervical plexuses, vagus nerve, sympathetic chain and lingual or recurrent laryngeal nerve. The nerve of origin was not identifi ed in six cases. Tumor enucleation was performed in 16 patients; the other fi ve required more extensive surgery. CONCLUSION: Schwannomas and neurofi bromas both derive from Schwann cells, but are different entities. They are solitary lesions, except in Von Recklinghausen’s disease. They are generally benign, and rarely recur. The recommended surgical treatment is tumor enucleation.